A imersão das consciências: a doutrina de segurança nacional e a cultura escolar na Escola Técnica Federal do Rio Grande do Norte (1968-1985) - Lima, Aline Cristina da Silva (2021)
The Brazilian military dictatorship, which began in April 1964, underwent a deepening of repressive violence and the State granted itself more powers with the enactment of Institutional Act No. 5. The military governments started, from then on, a process of denationalization of Brazilian education , marked by a series of agreements between the Ministry of Education and the North American Agency for International Development (USAID), which were part of the actions of the Alliance for Progress, led by the then president of the United States of America, Franklin Delano Roosevelt. These agreements inspired reforms at both higher and basic levels in Brazilian education. In the case of Professional Education, Law No. 5.524/68 was promulgated, which regulated the exercise of the profession of Industrial Technician of medium level. The so-called Federal Technical School of Rio Grande do Norte (ETFRN) was created in this scenario, its historical roots are related to the School of Apprentice Artifices, created in 1909 with the objective of training workers’ children for the labor market. At ETFRN, to meet the economic demands of Rio Grande do Norte (RN), courses such as electrical engineering, mechanics and buildings were created. We aim to analyze the relationship between the history of the ETFRN and the National Security Laws of 1967 and 1969, through the memories of teachers and students that bring meanings beyond regulations, decrees and laws. We start from the conceptions of oral history, in dialogue with Alessandro Portelli, Ana Maria Mauad and José Carlos Meihy; the concept of memory based on Maurice Halbwachs, Michael Pollack and Ecléia Bosi; and political culture, in line with Serge Berstein. The subjects’ narratives are related to documentary sources, such as newspapers, photographs, class diaries and educational legislation of the period. In conclusion, we emphasize that the ETFRN, while meeting the market’s demands, educated for obedience and maintenance of the order of the nation, with strict and disciplinary practices aligned with the National Security doctrine, as well as we emphasize that the relationship with the political culture of the dictatorship and the ETFRN school culture contributed to a history marked by disciplinarization, educational duality and conservative modernization. However, at the same time that the formation of students for the “know-how” was thought, there were student movements in search of free unions and more autonomy of the consolidated class, in 1985, with the creation of the Grêmio Djalma Maranhão, the enrollment of the first female student at the school in 1975, which substantially changed relations within the school and the creation of the art studio. By categorizing the interviews and relating them to our entire documentary apparatus, we point to the school as a sensitive space, capable of promoting the education of students beyond the interests of capital, as our interviewees signaled.